ANALISIS FISHING ACTIVITY KAPAL TUNA LONGLINE MENGGUNAKAN VESSEL MONITORING SYSTEM YANG BERBASIS DI BENOA BALI - Muhammad Irsyad Tawaqal; Roza Yusfiandayani; Mohammad Imron (Fakultas Perikanan dan Ilmu Kelautan, 2019)
Tuna fisheries based on Benoa fishing port has undergone major changes since 1993 when yellowfin tuna dominated the catch, followed by big eye tuna and other types of tuna. Fishing vessels to catch tuna in Benoa, Bali, are dominated by tuna longline, purse seine, and troll line vessels. Vessels that are up to 30 GT (>30 GT) must install the Vessels Monitoring System (VMS) to surveillance the fishing vessels that are operating following by the regulations. VMS data provide lot of data from vessel movment, but the problem is not used optimally and the analysis of data VMS still in development, therefore this research aims to identify the utilization VMS data for survilliance dan management of tuna longline based at Benoa. The method used was descriptive analysis using a spatial data management application. The results showed that VMS data can be used to know fishing activity such as vessel position, vessel velocity, and vessel movement. Fishing activity with VMS data can indentfy infraction did by tuna longline vessel that indicated transshipment activity, infraction of fishing area, and can used to validate data between logbook data and VMS data when the vessel landed a fish catch at port. Cross matching data between VMS and logbook data show that data suitability from 2016-2018 increase in 2016 suitability data get 53%, then 2017 get 94%, and 2018 get 98%.